An aggregate-level examination of the caseload pressure hypothesis - Wooldredge, John D. (Journal of quantitative criminology, 1989)
The idea that guilty pleas may be encouraged by time-conscious attorneys to process court caseloads expediently implies that some defendants may be influenced to forego their constitutional right to trial. If true, these defendants may be denied an adequate determination of legal guilt. Building on previous research, this paper presents a more thorough aggregate level test of the caseload pressure hypothesis than has previously been offered. Controlling for variation in structural and procedural characteristics across 101 Illinois circuit courts, this study supports the idea that felony caseload pressures significantly covary with felony guilty plea rates. Also, this relationship was stable between 1973 and 1984.